Association of Prenatal and Intrapartum Antibiotic Use with Risk of Childhood Atopic Dermatitis: A Systematic Review and Meta-Analysis - Yu-Chuan Chang; Hsing-Ju Wu; Meng-Che Wu (Children)
Background/Objectives: Atopic dermatitis (AD) is a chronic inflammatory skin condition with rising global prevalence. Increasing maternal antibiotic use during pregnancy has raised concerns about its potential link to childhood allergic diseases, including AD. However, existing meta-analyses have yielded inconsistent results. A systematic review and meta-analysis were conducted to investigate the association between prenatal antibiotic exposure, including intrapartum antibiotic prophylaxis (IAP), and the risk of AD developing in offspring. Methods: A systematic search protocol (PROSPERO ID: CRD42024577804) was conducted up to 29 August 2024, across the PubMed, Embase, and Cochrane databases. Cohort and case–control studies reporting associations between maternal antibiotic exposure during pregnancy or intrapartum and the risk of AD in offspring were included. Data were analyzed using RevMan Web and Comprehensive Meta-Analysis software. Results: Twenty studies involving 3,256,929 mother–child pairs were reviewed. The meta-analysis data demonstrated that prenatal antibiotic exposure was associated with AD in the main analysis (odds ratio [OR]: 1.12, 95% CI 1.03–1.21), but not in a separate analysis with a pooled hazard ratio (HR) (HR: 1.12, 95% CI 0.96–1.31). Trim-and-fill correction for significant publication bias (Egger’s test p = 0.003) in the main analysis resulted in a non-significant effect size (OR: 1.09, 95% CI 0.99–1.20). Subgroup analysis and meta-regression suggested that publication years and sample sizes contributed significant heterogeneity (p < 0.05). Regarding IAP and the risk of AD, no association was found (OR: 1.62, 95% CI 0.87–3.00). Conclusions: Current evidence in the existing literature does not support a positive relationship between antibiotic exposure, either during pregnancy or in the intrapartum period, and the risk of development of AD in offspring. However, substantial heterogeneity and the very low certainty of evidence limit the strength of our findings. Further studies that address confounders more thoroughly are needed to confirm these results.